KORKUT AND MODERNITY: SHAMANIC ARCHETYPE IN THE INTELLECTUAL HISTORY OF KAZAKHSTAN (Journal of history, 2025)
The article is devoted to the formation and development of the archetype of Korkut in the context of intellectual history of Kazakhstan. As the first shaman and storyteller, the inventor of the musical instrument kobyz, Korkut occupies a special place both in Kazakh science, including history, cultural anthropology and folkloristics, and in literature and art, including music and ballet. It also remains an important element linking Kazakhs to Turkic peoples through common origins in antiquity. The author traces the significance for Kazakh intellectual history and the history of ideas of the image of Korkut, The Book of Dede Korkut, as well as a set of legends among the peoples of Central Asia associated with the legendary burial place of Korkut Ata in the Kyzylorda region of the republic. The interdisciplinary approach to the material, сontent and comparative analyses of the texts allow us to reveal, firstly, the dynamics of the image of Korkut in the intellectual environment of Kazakhstan, reflecting cultural policy and historical processes, and secondly, several interpretative lines that unite Kazakh scientists and creative intellectuals and develop from the 19th century to the present day. Since the defining studies and statements were made during the Soviet era, this period is given special attention.
Keywords: Kazakhstan, Korkut, Korkut studies, Kazakh intelligentsia, intellectual history, cultural anthropology, modernisation, storytelling, shamanism, literature.